A novel mutation (F227L) arises in the reverse transcriptase of human immunodeficiency virus type 1 on dose-escalating treatment of HIV type 1-infected cell cultures with the nonnucleoside reverse transcriptase inhibitor thiocarboxanilide UC-781. - Balzarini, J; Pelemans, H; Esnouf, R; De Clercq, E (1998)
Treatment of wild-type human immunodeficiency virus [HIV-1(IIIB)]-infected cell cultures with the thiocarboxanilide UC-781 under low selective pressure (i.e., 0.01 microg/ml) resulted in the emergence of V106A RT mutant virus. On increasing drug concentrations (stepwise up to 30 microg/ml) the virus retained the V106A RT mutation but acquired the novel F227L mutation in the RT genome in addition to the L100I, K1O1I, and Y181C mutations. This multiple-mutant virus proved highly resistant to virtually all nonnucleoside RT inhibitors (NNRTIs) (e.g., nevirapine, delavirdine, and loviride), but retained full sensitivity to nucleoside analogs such as AZT, ddI, (-)FTC, and 3TC. The F227 amino acid is highly conserved in HIV-1 strains and forms part of the NNRTI-binding pocket. Our model suggests a hydrophobic interaction between F227 and the chloro atom of UC-781.